Scientific note: first global report of a bee nest built only with plastic - Allasino, Mariana Laura (2019)
Agricultural plastic waste can alter wildlife diversity and behavior. Species survival will depend on their ability to adapt to new environmental conditions. In a seed-producing farm, a Megachile sp. nest made fully with plastic was found in a trap nest. This record represents the first one worldwide on revealing the use of plastic in the total construction of a bee nest.